2014
DOI: 10.1002/jor.22671
|View full text |Cite
|
Sign up to set email alerts
|

Autologous protein solution prepared from the blood of osteoarthritic patients contains an enhanced profile of anti-inflammatory cytokines and anabolic growth factors

Abstract: The objective of this clinical study was to test if blood from osteoarthritis (OA) patients (n = 105) could be processed by a device system to form an autologous protein solution (APS) with preferentially increased concentrations of anti-inflammatory cytokines compared to inflammatory cytokines. To address this objective, APS was prepared from patients exhibiting radiographic evidence of knee OA. Patient metrics were collected including: demographic information, medical history, medication records, and Knee In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 35 publications
4
87
0
Order By: Relevance
“…In this study, APS was derived from control donors and tested on bovine cartilage explants which will not be the situation for patients being treated for OA. However, a recent study has demonstrated that APS from 105 OA patients contained high concentrations of anti‐inflammatory cytokines and growth factors similar to APS derived from healthy donors . Previous research has demonstrated that bovine and human cartilage explants similarly upregulate ECM degradation in a synergistic manner .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, APS was derived from control donors and tested on bovine cartilage explants which will not be the situation for patients being treated for OA. However, a recent study has demonstrated that APS from 105 OA patients contained high concentrations of anti‐inflammatory cytokines and growth factors similar to APS derived from healthy donors . Previous research has demonstrated that bovine and human cartilage explants similarly upregulate ECM degradation in a synergistic manner .…”
Section: Discussionmentioning
confidence: 92%
“…APS contains a statistically significant concentration increase of the following anabolic cytokines over baseline blood: EGF, IGF‐I, PDGF‐AB and ‐BB, VEGF, and TGF‐β1 . Furthermore, a recent study has measured elevated anabolic growth factor concentrations in the APS derived from 105 OA patients . The importance of synergistic growth factors on chondrocyte metabolism and subsequent cartilage growth has been previously demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…Another product of regenerative medicine and IL-1 receptor antagonist compound, autologous protein solution, has been described by O’Shaughnessey, et. al [20]. This was developed from the serum of patients with radiographic-proven osteoarthritis.…”
Section: Resultsmentioning
confidence: 99%
“…This was developed from the serum of patients with radiographic-proven osteoarthritis. Anti-inflammatory compounds isolated by immunosorbent assay in addition to IL-1 Ra include sIL-1RII, sTNF-RI, and sTNF-RII [20]. ,…”
Section: Resultsmentioning
confidence: 99%
“…Attempts have been made to employ individual recombinant inhibitors of IL‐1β or TNFα as treatments for OA, but these anti‐cytokines have failed to prove effective in OA clinical trials . In contrast, an Autologous Protein Solution (APS) prepared from a patient's own blood contains concentrated anti‐inflammatory cytokines, including interleukin‐1 receptor antagonist (IL‐1ra) and soluble forms of the cell receptors for IL‐1 and TNFα (sIL‐1RII and sTNF‐R) . IL‐1ra blocks the signaling of IL‐1β, sIL‐1RII competitively binds with IL‐1β, and sTNF‐RII binds to TNFα .…”
mentioning
confidence: 99%